The Effect of Comprehensive Sexual Education on Adolescent Behavior in Using Contraception : A Systematic Review - Dzakiyyah, Nurul; I'tishom, Reny (Journal of Community Medicine and Public Health Research, 2025)
Adolescence is a transition period from childhood to adulthood. This period is crucial because there are many physical and psychological changes. One issue that is quite rife in Indonesia is teenage pregnancy, which will ultimately lead teenagers to have abortions. The case above proves that it is essential to equip adolescents with the knowledge and skills to make responsible choices. Comprehensive Sexual Education (CSE) is believed to help solve this problem and achieve the Sustainable Development Goals (SDGs) by 2030, when CSE also conveys the importance of contraception and its benefits. The lack of systematic reviews of studies that highlight the effect of implementing Comprehensive Sexual Education on current contraceptive use makes researchers interested in conducting this systematic literature review. This research uses a Systematic Literature Review (SLR) using PICO (Population, Intervention/Issue, Comparison/Context, Outcome), and Boolean operators are used to facilitate searching studies. PRISMA flowcharts were used in this research until two studies were included in the analysis. Literature quality assessment was conducted using the quality assessment tool for quantitative studies from EPHPP (Effective Public Health Practice Project). Two cross-sectional studies were based in the United States. The sample sizes in studies range from 5000 to 7000. The results of this study show that comprehensive sexual education influences the use of contraceptives today, although it is not very significant. However, there are still many biases in this research. There is a need to conduct randomized controlled trials or multicenter cohort studies that use the same evaluation parameters to strengthen future systematic review research.